Memory dependent triple-phase-lag thermo-elasticity in thermo-diffusive medium - Yadav, Anand Kumar; Singh, Aarti; Jurczak, Paweł (Zielona Góra: Uniwersytet Zielonogórski)
The objective of the paper is to look at the propagation and reflection of plane waves in a thermo-diffusion isotropic medium. The reflection of plane waves in a thermo-diffusion medium was investigated in this study with reference to triple phase lag thermo-elasticity. The memory dependent derivative (MDD) is applied for this investigation. The fundamental equations are framed and solved for a particular plane.
Keywords: diffusion; triple phase lag thermo-elasticity; reflection coefficients; memory dependent derivative (MDD)